PERAN REWARD AND PUNISHMENT DALAM MENINGKATKAN LITERASI PEMBELAJARAN EKONOMI MELALUI PENDIDIKAN BER-PANCASILA DENGAN MENINGKATKAN RASA NASIONALISME MAHASISWA - Yopi Nisa Febianti (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
AbstractThis article is about the research conducted to find out the role of reward and punishment in improving economic learning literacy through Pancasila education by increasing students' sense of nationalism. This study used qualitative research methods. The data sources of this study are primary and secondary data. Primary data are questionnaires totaling 26 statements that are distributed to students, while secondary data are observation sheets, interview sheets, as well as documentation (photo). The participants of this study were first-level students of the Economics Education program of FKIP Unswagati who took 30 Macroeconomic Theory courses with 30 people. Data analysis was conducted qualitatively with domains, taxonomies, components, and cultural themes. The results of the analysis show that giving positive rewards and punishments, especially giving light and favorable sentences, can improve literacy in economic learning, so that the atmosphere of the lecture becomes more conducive and enjoyable. Increasing student economic learning literacy is achieved through Pancasila education by practicing Pancasila values in daily life, including during lectures in class. Giving punishment by singing national songs is a way to arouse the love of the homeland. Singing national songs is one of the ways lecturers try to improve the nationalism of students, so that the love of the country continues to thrive in the soul of Indonesia's young generation, namely students. The conclusion of this study is that the role of reward and punishment is very important in improving economic learning literacy that is seen continuously from the enthusiasm and activeness of student learning based on the practice of Pancasila values in which there are moral values and aesthetic values, in addition to divine values as the basis and value of justice as a goal, so as to increase the sense of nationalism of students in a conducive and pleasant learning atmosphere, serious and focused learning, but relaxed.Keywords :Â Role of reward and punishment, Literacy of economic learning, Pancasila education, Sense of nationalism.Â